Lampreys of Ukraine as a prospective object of cryobiological research - Ostras, Daniil; Honcharov, Hennadii; Mikson, Kostiantyn (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):296